Customers and patrons of the mad-trade : the management of lunacy in eighteenth-century London : with the complete text of John Monro's 1766 case book - Andrews, Jonathan, 1961-; Scull, Andrew, 1947- (Medicine and society, 2003)
This book is a lively commentary on the eighteenth-century mad-business, its practitioners, its patients (or ""customers""), and its patrons, viewed through the unique lens of the private case book kept by the most famous mad-doctor in Augustan England, Dr. John Monro (1715-1791). Monro's case book, comprising the doctor's jottings on patients he saw in the course of his private practice--patients drawn from a great variety of social strata--offers an extraordinary window into the subterranean world of the mad-trade in eighteenth-century London. The volume concludes with a complete